Pectin edible coatings enriched with essential oils of lemon and thyme to improve storage of black raspberry - Abdi, Soma; Bakhshi , Davood (Journal of Postharvest Technology, 2019)
The short-term postharvest durability of black raspberry is often due to containing a high level of water, high metabolic activity and sensitivity to fungi. In  order to increase the quality and storage longevity of black raspberry fruit, the effects of different densities of improved pectin coating with lemon and  thyme essential oils and also thyme essential oils accompanied with edible pectin coating in 5°C for a period of 12 days has been studied. The  experiment has been done with 6 different treatments including control without coating (distilled water) in three replications based completely  randomized design which goes as follows: P2%+TE 0.15% (W/V), P2 TE 1 %+ (W/V), P2%+LE 0/15%(W/V), P2%+ LE0.1% (W/V). Fruit quality during  storage was evaluated at 3-days intervals in terms of marketability, weight loss, anthocyanin content, vitamin C, TA and TSS. According to the results,  coating fruits with pectin along with lemon essential oils oil delayed degradation of anthocyanin, vitamin C. All coating treatments have delayed the  weight loss in the fruits by means of controlling losing fruit moisture in postharvest storage condition. The best result was gained in P2%+TE 0.15%  treatment of a decrease in weight loss. Also the longest postharvest storage time belonged to treatment P2%+ LE 0.15%. Besides, the enriched pectin  coating with lemon and thyme essential oils had a positive effect on preserving the quality of the appearance of the fruit in the storage period. Also the  highest amount of vitamin C and anthocyanin for the mentioned treatment was resulted for a period of 12 days. According to the results, pectin coating,  enriched by lemon and thyme essential oils is a good treatment for preserving the quality of shelf-life of black raspberry fruit.
Keywords: Anthocyanin; postharvest; weight loss; quality; storage